Analisis Penugasan Guna Meminimumkan Waktu Pengiriman Produk Menggunakan Metode Hungarian pada UKM Roti ZB Cikampek - Arafat, Yasir; Suseno, Agustian (UNISTEK, 2021)
UKM Roti ZB is a company engaged in the food sector. The problem that is being faced by the company is the assignment of product delivery to consumers, each employee is facilitated by the same means of transportation but has a different delivery time. The purpose of this study is to determine the efficiency of the resulting delivery time using the Hungarian method, as well as to provide settlement arrangements for employee placement in product delivery to consumers based on the Hungarian method. This study uses the Hungarian method and POM-QM for Windows software. Based on the research that has been done, the result is that the total time of product delivery before using the Hungarian method is 89 minutes, while if using the Hungarian method is 85 minutes. So that the time efficiency obtained when using the Hungarian method is 4 minutes. Then there are differences in product delivery assignments before using the Hungarian method, namely Doni to deliver products to Cibuaya, Rahmad to Cilaber, Wawan to Jayakerja, Aldi to Banyusari, and Irwan to Jatisari. Meanwhile, if you use the Hungarian method for Doni for Cilaber, Rahmad for Cibuaya, Wawan for Banyusari, Aldi for Jayakerja, and Irwan for Jatisari.